Socio-Economic Conditions of "Aron Jeruk" Family in Kabanjahe District, Karo Regency - Purba, Haris Aditya Putra; Mujahiddin, Mujahiddin (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
The socio-economic conditions of the orange aron family in Kabanjahe District still face various challenges due to the instability of work as casual laborers. Their income depends on the harvest season and weather conditions, making it difficult to meet their daily needs. These economic limitations also have an impact on various aspects of their lives, such as education, health, and also housing. This study aims to analyze and describe the socio-economic conditions of the orange aron family, focusing on the factors that influence their well-being amidst job uncertainty. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and document analysis to obtain relevant information about the daily lives of the aron. The results of this study indicate that the income of the aron family is unstable, so they have to adapt in various ways to meet their needs in terms of education, health, and also housing.